2018
DOI: 10.1111/nph.15104
|View full text |Cite
|
Sign up to set email alerts
|

Key questions and challenges in angiosperm macroevolution

Abstract: Contents Summary 1170 I. Introduction 1170 II. Six key questions 1172 III. Three key challenges 1177 IV. Conclusions 1181 Acknowledgements 1182 References 1183 SUMMARY: The origin and rapid diversification of angiosperms (flowering plants) represent one of the most intriguing topics in evolutionary biology. Despite considerable progress made in complementary fields over the last two decades (paleobotany, phylogenetics, ecology, evo-devo, genomics), many important questions remain. For instance, what has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 210 publications
(303 reference statements)
4
109
0
Order By: Relevance
“…Our study allowed to clarify a long-standing question 2 , but such reconstruction necessarily comes with limitations. Nevertheless, this is a major step forward in understanding the ancestral chromosome number for angiosperms, and we believe that this issue should be added to the angiosperm macroevolutionary agenda 34 . Progress in reconstructing the ancestral chromosome number may require the development of models that include heterogeneity in the patterns of chromosome evolution across a phylogenetic tree 23 , along with a deeper insight into genome and karyotype evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Our study allowed to clarify a long-standing question 2 , but such reconstruction necessarily comes with limitations. Nevertheless, this is a major step forward in understanding the ancestral chromosome number for angiosperms, and we believe that this issue should be added to the angiosperm macroevolutionary agenda 34 . Progress in reconstructing the ancestral chromosome number may require the development of models that include heterogeneity in the patterns of chromosome evolution across a phylogenetic tree 23 , along with a deeper insight into genome and karyotype evolution.…”
Section: Resultsmentioning
confidence: 99%
“…The apparent stability of the Annona genome over time is notable given that gene family expansion (such as in (Chaw et al 2019 increase of transposable elements (Belyayev 2014;Joly-Lopez and Bureau 2018) and WGD events (Hoffman et al 2012) are potential triggers of morphological or adaptive key innovations and rapid diversification (Tank et al 2015;Soltis and Soltis 2016). These aspects raise further questions regarding the origin and evolutionary mechanisms giving rise to the diversity of magnoliids (Sauquet and Magallón 2018). The slow but regular reduction in population size of Annona muricata is compatible with the Quaternary contraction of tropical regions in several parts of the world, and suggests that the soursop could be severely affected by climate changes, as may other tropical taxa.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of flowering plants (angiosperms) was a geologically sudden and ecologically transformative event in the history of life. Recent analyses have suggested that the major angiosperm clades diverged in quick succession within the Cretaceous, with monocots, magnoliids and eudicots starting to diversify within ca 5 Ma (Sauquet and Magallón 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of diversification rates have shed light on potential drivers of diversity gradients across wide phylogenetic and geographic scales (Jetz et al, 2012; Rabosky et al, 2018; Landis et al, 2018). However, inferring diversification processes based solely on extant species phylogenies is very challenging (Etienne et al, 2011; Didier et al, 2017; Sauquet and Magallón, 2018; Mitchell et al, 2019), and the accuracy of these methods is an area of intensive research and heated controversy (O’Meara and Beaulieu, 2016; Moore et al, 2016; Rabosky et al, 2017; Meyer et al, 2018; Rabosky, 2018). Many contemporary analytical workflows for studying diversification have seen little vetting to date with empirical datasets (but see Title and Rabosky, 2017), and much remains to be explored about the response of diversification methods to missing and biased species sampling (Sauquet and Magallón, 2018).…”
Section: Introductionmentioning
confidence: 99%